EU member state exit: understanding EU disintegration through aggregation - Andraos, Martine (2022)
After Brexit and the major crises that impacted the European Union, debates about the polity’s disintegration have been triggered, and questions on which state might be the next to leave have intensified. We ask, which factors lead an EU member state to have an orientation to exit? In this dissertation, we conceptualize EU disintegration by bringing the EU member state back to the core of the EU’s raison-d’etre and design a matrix for EU disintegration studies, where the EU member state is presented as the fate holder of the EU. The matrix specifies that for an EU state to exit the EU, it has to go through a four-step path; on a domestic level, an EU member state witnesses an orientation to exit, then, an anti-EU veto players constellation leads to invoking Article 50 of the TFEU. Afterwards, at the intergovernmental level, a negotiation based on bargaining power determines the exit terms, then, the EU veto players constellation results in an exit. Additionally, we employ the three theories of EU integration to theoretically frame the study: Liberal-Intergovernmentalism, Neo-Functionalism, and Post-Functionalism. Although commonly perceived as contradicting theories, we argue that none of the three is enough to theorize EU disintegration, but rather the three of them, in a complementary manner. We empirically assess the period from 2008 to 2020 by identifying a list of variables, which we aggregate in nine indicators that form three relevant indices, which are then aggregated by computing the Principal Component PC, to quantify the first step of the four-step path; the EU Member State Orientation to Exit Index. We compare the results of the aggregation using the Principal Component Analysis by averaging and summing-up up the nine indicators. The index is used to forecast which state could fulfil the first required step of the path to EU Exit.
Keywords: Europäische Union; Hochschulschrift